Teff Grass Response to Nitrogen Fertilization - J. D. Holman; D. H. Min; S. Maxwell (Kansas Agricultural Experiment Station Research Reports, 2015)
Teff, a warm season annual grass native to Africa, is gaining popularity as a forage crop in the United States. Little information regarding nitrogen fertilization is available for teff grass production. This field experiment was conducted to evaluate teff grass response to varying nitrogen fertilization rates under dryland conditions. There was no yield response to increasing nitrogen rate or nitrogen source applied.
Keywords: teff; annual forages; nitrogen fertilization; soil fertility